The presence of repetitive strain injury, work-related musculoskeletal pain and the stress index in employees of a poultry slaughterhouse (Research, Society and Development, 2024)
High levels of stress harm the quality of life of employees, who tend to have more occupational diseases such as: RSI and WMSDs. This research aimed to observe and quantify the presence of repetitive strain injury (RSI) or work-related musculoskeletal pain (WMSD), and the stress index in employees at a poultry slaughterhouse. To this end, two questionnaires were administered. The sample was made up of 56 employees from a poultry slaughterhouse, located in the Northeast region of Rio Grande do Sul, divided into three groups, G1 kids room with 31 individuals, G2 secondary packaging with 15 employees and G3 administrative sector with 10 employees, of both sexes. Those evaluated present muscle pain and/or discomfort, in generalized areas in both sexes, with different percentages of incidence. It is noteworthy that the offal sector had a higher complaint rate compared to the other sectors evaluated. The wrist, hand, forearm, shoulder, lumbar and dorsal regions were those with the greatest indications of pain and discomfort, in both sexes, however, with greater indications for the female public. Little stress was detected within the evaluated sectors, with high and very high stress levels being more diagnosed in the giblets room.